Level of Information and Education Campaign on Solid Waste Management and Household Practices on Solid Waste Disposal in Butuan City - Herrera, Fernando T.; Boyles, Lilia Z.; Miculob, Ian G. (JPAIR Multidisciplinary Research, 2012)
This study investigates the level of Information and Education Campaign (IEC) on Solid Waste Management (SWM) conducted by the LGU and other government agencies in Butuan City. Moreover, it also considered the practices among households of Butuan City in relation to solid waste disposal. Descriptive survey design was used in this study. Using the stratified random sampling, ten (10) communities were selected with households as the main unit of analysis. From eighty-six (86) legitimate communities of Butuan City, five (5) communities were randomly selected from each of the rural and urban communities as classified by NEDA. Results revealed that, the level of IEC in both rural and urban communities of Butuan City was poor. Public forum or general assembly, focus group discussion, installation of tarpaulin and other signs, television ad and radio broadcast, house to house information campaign, and school campaign were seldom carried out. Lack of institutional support and inadequate provision of garbage disposal points and Mass Recovery Facilities (MRF) from other concerned government agencies, nongovernment organizations and HEIs were evident. It was also reported that majority of the households had their own garbage storage bin with considerable number of them having separators for biodegradable and non-biodegradable wastes. Some opted to use plastic bags and sacks instead. Many of those in rural areas buried their biodegradable and non-biodegradable waste on the ground.